Peningkatan Kesadaran Hidup Sehat Masyarakat melalui Senam Aerobic Low Impack sebagai Upaya Pencegahan dan Penanganan Hipertensi pada Lansia - Durrotun Nafisah; Mariana Mariana (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The elderly complain of dizziness and difficulty sleeping due to lack of exercise and lack of knowledge or experience. One of the degenerative diseases that often appear without symptoms is hypertension. Hypertension is also called the silent killer because it can appear without symptoms. Hypertension in the elderly can be reduced with low impact aerobic exercise. The exercise is a light exercise performed by the elderly which causes relaxation to reduce complaints of dizziness caused by hypertension. This study aims to determine the changes before and after the effectiveness of low impact aerobic exercise on changes in blood pressure in the elderly. This research method uses the ABCD (Asset Base Community Development) method. The population in this study were elderly people in Tegalrejo Hamlet, Tegalrejo Village, Pulung District, Madiun Regency. This activity includes surveys, and carrying out socialization on efforts to prevent and treat hypertension in the elderly. The result of community service activities is an increase in awareness and understanding of the elderly about hypertension, especially efforts to prevent and treat it